Attachment and Interpersonal Theory and Group Therapy: Two Sides of the Same Coin. Issue 2 (3rd April 2017) - Whittingham, Martyn
ABSTRACT: Attachment and interpersonal theories and therapies have significant overlap, in terms of both theoretical underpinnings and overlapping factor structure of the instruments used. This article discusses how group theories and therapies utilize this common conceptual framework both in well-established and newer approaches.